The Maud Belt (East Antarctica) as an accretionary orogen in Rodinia: Isotopic composition, evolution and spatial variation - Wang, Cheng-Cheng; Jacobs, Joachim; Marschall, Horst R.; Hemming, Sidney; Jacques, Guillaume; Läufer, Andreas (Gondwana Research, 2025)
The Maud Belt of East Antarctica represents a late Mesoproterozoic orogen along the periphery of the Proto-Kalahari Craton, and a better understanding of its orogenic nature helps to elucidate the configuration of Kalahari within the Rodinia supercontinent. In this study, we present original and compiled zircon U–Pb geochronological and Hf isotopic data spanning ca. 1180 to 950 Ma along with whole-rock Nd isotopes, covering a broad expanse of the Maud Belt and the adjacent Archean Grunehogna Craton, in an attempt to delineate the spatial and temporal patterns of isotopic compositions and evolution, and to better understand the orogenic architecture and style. Spatial isotopic variations are particularly evident in the western front of the orogen (western H.U. Sverdrupfjella) in contrast to other regions. The former exhibits a wide range of isotopic compositions, with the majority showing highly evolved signatures, indicating that the orogenic crust developed through the reworking of pre-existing Archean–Paleoproterozoic continental crust. In contrast, most other regions of the Maud Belt are characterized by relatively juvenile Hf and Nd isotopic compositions, which are interpreted to be derived from a mixture of juvenile magmas and Paleoproterozoic crust. The Hf isotopic evolution from 1180 Ma to 950 Ma indicates significantly less reworking of pre-existing continental crust compared to other contemporaneous Rodinia-forming orogens, including the Grenville Orogen itself, and emphasizes a predominant addition of juvenile material, implying a continuous subduction process. The isotopic investigation in this study, combined with the geological and paleomagnetic evidence, indicates that the Maud Belt most likely represents an exterior accretionary orogen along the eastern margin of the Proto-Kalahari Craton, rather than being part of the continental collision zones that led to Rodinia amalgamation.
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi; paleogeografi; paleomagnetisme

The foraging distribution and habitat use of chick-rearing snow petrels from two colonies in Dronning Maud Land, Antarctica - Honan, Eleanor Maedhbh; Wakefield, Ewan D.; Phillips, Richard A.; Grecian, W. James; Prince, Stephanie; Robert, Henri; Descamps, Sébastien; Rix, Anna; Hoelzel, A. Rus; McClymont, Erin L. (Marine Biology, 2025)
The polar sea-ice zones are highly productive and seasonal habitats that support large populations of vertebrate predators. In the Antarctic, snow petrels (Pagodroma nivea) are regarded as highly ice-dependant, yet knowledge of their habitat use and foraging distribution during the breeding period comes largely from ship-based observations. Snow petrels show sexual size dimorphism, and previous studies have demonstrated a degree of sexual segregation in habitat use in East Antarctica during the incubation period. Here, we characterise the movements, behaviour and habitat use of foraging snow petrels using bird movement and remotely sensed environmental data. We tracked snow petrels from two colonies in Dronning Maud Land, East Antarctica during early chick rearing in January to February 2022, a period of unusually rapid sea-ice retreat in the region. During the chick-rearing period, mean foraging range was c. 395 km and did not differ between the sexes. However, we found some evidence of differing habitat use between the sexes: males foraged more in areas of higher sea-ice concentration and over the continental shelf, while females utilized deeper waters and lower sea-ice concentrations. Sexes also diverged in their behavioural responses to both sea ice and depths, with males more likely to switch to foraging in areas of higher sea-ice concentrations than females and females more likely to switch to foraging in deeper waters than males. Although both sexes were more likely to forage at higher sea-ice concentrations, they also used areas with little or no sea ice. This contrasts with previous studies and may have been due to the unusual paucity of sea-ice cover during our tracking period.
Keywords: Dronning Maud Land; klimaendringer; marin biologi; ornitologi; petreller; sjøfugler; zoologi

Evidence of active subglacial lakes under a slowly moving coastal region of the Antarctic Ice Sheet - Arthur, Jennifer F.; Shackleton, Calvin; Moholdt, Geir; Matsuoka, Kenichi; van Oostveen, Jelte (The Cryosphere, 2025)
Active subglacial lakes beneath the Antarctic Ice Sheet provide insights into the dynamic subglacial environment, with implications for ice-sheet dynamics and mass balance. Most previously identified lakes have been found upstream (>100 km) of fast-flowing glaciers in West Antarctica, and none have been found in the coastal region of Dronning Maud Land (DML) in East Antarctica. The regional distribution and extent of lakes as well as their timescales and mechanisms of filling–draining activity remain poorly understood. We present local ice surface elevation changes in the coastal DML region that we interpret as unique evidence of seven active subglacial lakes located under slowly moving ice near the grounding line margin. Laser altimetry data from ICESat-2 and ICESat (Ice, Cloud, and Land Elevation Satellites) combined with multi-temporal Reference Digital Elevation Model of Antarctica (REMA) strips reveal that these lakes actively fill and drain over periods of several years. Stochastic analyses of subglacial water routing together with visible surface lineations on ice shelves indicate that these lakes discharge meltwater across the grounding line. Two lakes are within 15 km of the grounding line, while another three are within 54 km. Ice flows 17–172 m a−1 near these lakes, much slower than the mean ice flow speed near other active lakes within 100 km of the grounding line (303 m a−1). Our results improve knowledge of subglacial meltwater dynamics and evolution in this region of East Antarctica and provide new observational data to refine subglacial hydrological models.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; glasiologi; innlandsis; isstrøm; satellite altimetri; subglasial innsjø

Brief communication: Annual variability of the atmospheric circulation at large spatial scale reconstructed from a data assimilation framework cannot explain local East Antarctic ice rises' surface mass balance records - Cavitte, M. G. P.; Goosse, H.; Dalaiden, Q.; Ghilain, N. (The Cryosphere, 2025)
Ice cores are influenced by local processes that alter surface mass balance (SMB) records. To evaluate whether atmospheric circulation on large spatial scales explains the differing SMB trends at eight East Antarctic ice rises, we assimilated ice core SMB records within a high-resolution downscaled atmospheric model, while incorporating radar-derived SMB constraints to quantify local observation errors. The reconstruction captures the diverse variability from SMB records but may over-fit by introducing unrealistic wind spatial heterogeneity. While local errors are quantified, they might not cover all uncertainties. Moreover, small-scale wind circulation, unresolved in the reconstruction, could significantly affect local ice core SMB signals.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; iskjerner; klimamodeller; kryosfæren; meteorologi

Strong turbulent flow in the subauroral region in the Antarctic can deteriorate satellite-based navigation signals - Kotova, D. S.; Sinevich, A. A.; Chernyshov, A. A.; Chugunin, D. V.; Jin, Y.; Miloch, W. J. (Scientific Reports, 2025)
In the subauroral zone at the boundary of the auroral oval in the evening and night hours during geomagnetic disturbances, a narrow (about 1°–2°) and extended structure (several hours in longitude) is formed. It is known as a polarization jet (PJ) or the subauroral ion drift (SAID). The PJ/SAID is a fast westward ion drift and is one of the main signatures of a geomagnetic disturbance in the subauroral ionosphere at the altitudes of the F-layer, when the geomagnetic AE index reaches more than 500 nT. Plasma speed in the PJ/SAID can reach several kilometres per second, and the size of plasma irregularities inside it can reach scales from tens of meters to several hundred meters. Such high velocities and structured plasma can affect trans-ionospheric radio waves and lead to scintillations in the received signal. We show that at the moment of auroral activity intensification, an increase in the magnitude of phase scintillation index (σϕ) as well as loss of satellite signals lock were observed in the region of the PJ/SAID equatorward of the auroral oval over Dronning Maud Land (Queen Maud Land) in Antarctica. We find that fluctuations inside the PJ/SAID can lead to serious deterioration of radio communication or navigational services. We emphasize the importance of considering the geometry of the beam passing from the GNSS satellite to the receiver on the ground. We highlight the mutual contribution of the PJ/SAID and the diffuse aurora boundary, which are almost impossible to separate in practice. Our results demonstrate the importance of considering the subauroral zone, where very dynamic plasma formations can occur with a strong flow and various-scale irregularities inside that lead to serious interference in satellite communications.
Keywords: Dronning Maud Land; aurora; fysikk; geomagnetiske stormer; ionosfæren; magnetosfæren; romfysikk; sørlys

Basal Melting and Oceanic Observations Beneath Central Fimbulisen, East Antarctica - Lindbäck, Katrin; Darelius, Elin; Moholdt, Geir; Vaňková, Irena; Hattermann, Tore; Lauber, Julius; de Steur, Laura (Journal of Geophysical Research: Oceans, 2025)
Abstract Basal melting of ice shelves is fundamental to Antarctic ice sheet mass loss, yet direct observations remain sparse. We present the first year-round melt record (2017-2021) from a phase-sensitive radar on Fimbulisen, one of the fastest flowing ice shelves in Dronning Maud Land, East Antarctica. The observed long-term mean ablation rate at 350 m depth below the central ice shelf was 1.0 ± 0.5 m yr?1, marked by substantial sub-weekly variability ranging from 0.4 to 3.5 m yr?1. 36-h filtered basal melt rate fluctuations closely align with ocean velocity. On seasonal time scales, melt rates peak during austral spring to autumn (September-March), driven by both elevated ocean velocities and thermal driving near the base. The combined effect of thermal driving and current speed explains the majority of the melt rate variability (r = 0.84), highlighting the dominant role of shear-driven turbulence. This relationship enables parameterization of melt rates for the decade-long ocean record (2010?2021), although deviations appear under low and high forcing conditions. Both observed and parameterized melt rates show similar yearly mean magnitudes compared to satellite-derived melt rates but with a tenfold lower seasonal amplitude and a 3-month delay in seasonality. These detailed concurrent ice?ocean observations provide essential validation data for remote sensing and numerical models that aim to quantify and project ice-shelf response to a change in ocean forcing. In situ measurements and continued monitoring are crucial for accurately assessing and modeling future basal melt rates, and for understanding the complex dynamics driving ice-shelf stability and sea-level change.
Publisher: John Wiley & Sons, Ltd Article number: e2023JC020506
Keywords: Dronning Maud Land; fjernmåling; klimamodeller; oseanografi

Katabatic and foehn winds control the distribution of supraglacial lakes in Dronning Maud Land, Antarctica - Mahagaonkar, Anirudha; Moholdt, Geir; Glaude, Quentin; Schuler, Thomas V. (Earth and Planetary Science Letters, 2025)
Meltwater ponding along the margins of Antarctica poses a threat to ice shelf stability, increasing the risk of accelerated inland ice mass loss. Understanding the key drivers of supraglacial lake formation is therefore essential for assessing the vulnerability and future stability of Antarctic ice shelves. In this study, we combine high-resolution simulation from the regional climate model Modèle Atmosphérique Régional (MAR) with satellite-derived records of supraglacial lakes in coastal Dronning Maud Land to investigate the role of topographic downslope winds on spatial lake distribution. We find that persistent katabatic winds and episodic foehn winds are key controls on the observed regional patterns of lakes. Katabatic winds, most persistent in eastern Dronning Maud Land, exert a sustained impact near grounding zones through snow erosion, scouring and sublimation. Foehn winds predominantly affect ice shelves on the lee (western) side of large ice rises and promontories, causing considerable surface warming. While these downslope winds directly contribute to surface melt and ponding during summer, they also precondition the surface year-round through wind-driven warming and sublimation. Statistical analysis of downslope wind exposure further allows us to identify other Antarctic ice shelves that may become vulnerable to future ponding as firn retention capacity is diminished.
Article number: 119482
Keywords: Dronning Maud Land; glasiologi; isshelf; klimamodeller; klimatologi; kryosfæren; meteorologi; subglasial innsjø

Dispersal and habitat preference of juvenile emperor penguins—implications for conservation management - Makhado, Azwianewi Benedict; Crawford, Robert J. M.; Dyer, Bruce M.; Masotla, Makhudu; Lowther, Andrew (Royal Society Open Science, 2025)
Seabirds can disperse widely when searching for prey, particularly during nonbreeding periods. Conservation measures predominately focus on protecting breeding colonies, while spatial protection at sea is often based on knowledge of the distribution of breeding adults, despite accumulating evidence that marine habitats used by immature birds sometimes differ from those of adults. Juvenile emperor penguins from Atka Bay, west Dronning Maud Land, Antarctica, tracked immediately after fledging performed long migrations to the northern extents of the Convention for the Conservation of Antarctic Marine Living Resources subareas 48.4 and 48.6. Individuals did not remain long at their northern positions, before commencing a rapid southerly movement to within a few hundred km of the marginal ice zone (MIZ). The initial migratory movement was broadly synchronous across individuals. The southward movement and subsequent change to area-restricted searching were consistent with the MIZ representing a potentially important feeding habitat for juvenile emperor penguins. Spatio-temporal management mechanisms may be beneficial in reducing threats to these young penguins.
Publisher: Royal Society Article Number: 231800
Keywords: Dronning Maud Land; biologi; marine økosystemer; ornitologi; pingviner; sjøfugler; telemetri; økologi

Enhanced basal melting in winter and spring: seasonal ice–ocean interactions at the Ekström Ice Shelf, East Antarctica - Zeising, O.; Hattermann, T.; Kaleschke, L.; Berger, S.; Boebel, O.; Drews, R.; Ershadi, M. R.; Fromm, T.; Pattyn, F.; Steinhage, D.; Eisen, O. (The Cryosphere, 2025)
Basal melting of Antarctic ice shelves significantly contributes to ice sheet mass loss, with distinct regional disparities in melt rates driven by ocean properties. In Dronning Maud Land (DML), East Antarctica, cold water predominantly fills the ice shelf cavities, resulting in generally low annual melt rates. In this study, we present a 4-year record of basal melt rates at the Ekström Ice Shelf, measured using an autonomous phase-sensitive radio-echo sounder (ApRES). Observations reveal a low mean annual melt rate of 0.44 m a−1, with a seasonal variability. Enhanced melting occurs in winter and spring, peaking at over 1 m a−1, while rates are decreased in summer and autumn. We hypothesise that the dense water formed during sea-ice formation erodes the water column stratification during late winter and spring, leading to an increase in the buoyancy of the ice shelf water plume. An idealised plume model supports this hypothesis, indicating that the plume velocity is the primary driver of seasonal basal melt rate variability, while changes in ambient water temperature play a secondary role in the range of oceanographic conditions that are observed below the Ekström Ice Shelf. These findings offer new insights into the dynamics of ice–ocean interactions in East Antarctica, emphasising the need for further observations to refine our understanding of ocean variability within ice shelf cavities and improve assessments of ice shelf mass balance.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; ekkolodd; glasiologi; havis; isshelf; oseanografi; sjøis

Enhanced basal melting in winter and spring: seasonal ice–ocean interactions at the Ekström Ice Shelf, East Antarctica - Zeising, O.; Hattermann, T.; Kaleschke, L.; Berger, S.; Boebel, O.; Drews, R.; Ershadi, M. R.; Fromm, T.; Pattyn, F.; Steinhage, D.; Eisen, O. (The Cryosphere, 2025)
Basal melting of Antarctic ice shelves significantly contributes to ice sheet mass loss, with distinct regional disparities in melt rates driven by ocean properties. In Dronning Maud Land (DML), East Antarctica, cold water predominantly fills the ice shelf cavities, resulting in generally low annual melt rates. In this study, we present a 4-year record of basal melt rates at the Ekström Ice Shelf, measured using an autonomous phase-sensitive radio-echo sounder (ApRES). Observations reveal a low mean annual melt rate of 0.44 m a−1, with a seasonal variability. Enhanced melting occurs in winter and spring, peaking at over 1 m a−1, while rates are decreased in summer and autumn. We hypothesise that the dense water formed during sea-ice formation erodes the water column stratification during late winter and spring, leading to an increase in the buoyancy of the ice shelf water plume. An idealised plume model supports this hypothesis, indicating that the plume velocity is the primary driver of seasonal basal melt rate variability, while changes in ambient water temperature play a secondary role in the range of oceanographic conditions that are observed below the Ekström Ice Shelf. These findings offer new insights into the dynamics of ice–ocean interactions in East Antarctica, emphasising the need for further observations to refine our understanding of ocean variability within ice shelf cavities and improve assessments of ice shelf mass balance.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; glasiologi; oseanografi

Features and processes of rock weathering in central Dronning Maud Land, Antarctica - Elvevold, Synnøve; Engvik, Ane K.; Sunde, Øyvind (Geomorphology, 2024)
In this study, we have investigated rock weathering phenomena in the central part of Dronning Maud Land, Antarctica. The area is characterized by low mean annual temperatures (−18 °C), strong katabatic winds, and minimal liquid water at the surface. Weathering features, including ventifacts, tafoni, and grus accumulations, are characterized through field observations, rock surface temperature measurements, and microscopic analysis. Abrasion by sand and ice particles transported by strong winds has locally resulted in ridge-shaped ventifacts and rock surfaces with elongated pits, furrows, and grooves. The abrasion-caused features, such as polished facets, keels, and grooves, indicate a northeast-facing wind direction, aligning with the present-day wind regime. The dominant weathering processes in coarse-grained intrusive rocks are oxidation and granular disintegration. Fe-oxidation induces cracking, increasing the porosity and enhancing susceptibility to further weathering. Additionally, temperature fluctuations on rock surfaces caused by solar radiation create thermal stress, which can lead to the formation of microcracks. These microcracks, formed due to thermal expansion, are likely to propagate through subcritical cracking, which is a slow, long-term process. Together, Fe-oxidation, thermal expansion, and subcritical cracking are important mechanisms contributing to long-term weathering and rock decay. Salt weathering, facilitated by snow and ice meltwater, particularly within tafoni, leads to flaking and disintegration of the parent rock. These findings shed light on the complex interactions shaping the geomorphology of central Dronning Maud Land and provide insights into long-term weathering processes operating in Antarctica's extreme environment.
Article number: 109435
Keywords: Dronning Maud Land; geologi; geomorfologi

Radar internal reflection horizons from multisystem data reflect ice dynamic and surface accumulation history along the Princess Ragnhild Coast, Dronning Maud Land, East Antarctica - Koch, Inka; Drews, Reinhard; Franke, Steven; Jansen, Daniela; Oraschewski, Falk Marius; Muhle, Leah Sophie; Višnjević, Vjeran; Matsuoka, Kenichi; Pattyn, Frank; Eisen, Olaf (Journal of Glaciology, 2024)
Ice shelves, which regulate ice flow from the Antarctic ice sheet towards the ocean, are shaped by spatiotemporal patterns of surface accumulation, surface/basal melt and ice dynamics. Therefore, an ice dynamic and accumulation history are imprinted in the internal ice stratigraphy, which can be imaged by radar in the form of internal reflection horizons (IRHs). Here, IRHs were derived from radar data combined across radar platforms (airborne and ground-based) in coastal eastern Dronning Maud Land (East Antarctica), comprising three ice rises and adjacent two ice shelves. To facilitate interpretation of dominant spatiotemporal patterns of processes shaping the local IRH geometry, traced IRHs are classified into three different types (laterally continuous, discontinuous or absent/IRH-free). Near-surface laterally continuous IRHs reveal local accumulation patterns, reflecting the mean easterly wind direction, and correlate with surface slopes. Areas of current and past increased ice flow and internal deformation are marked by discontinuous or IRH-free zones, and can inform about paleo ice-stream dynamics. The established IRH datasets extend continent-wide mapping efforts of IRHs to an important and climatically sensitive ice marginal region of Antarctica and are ready for integration into ice-flow models to improve predictions of Antarctic ice drainage.
Edition: 2023/12/12 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; Sørishavet; glasiologi; isshelf; teknologi

Permafrost and ground-ice conditions in the Untersee Oasis, Queen Maud Land, East Antarctica - Lacelle, Denis; Verret, Marjolaine; Faucher, Benoit; Fisher, David; Gaudreau, Adam; Pellerin, André; Ecclestone, Miles; Andersen, Dale T. (Antarctic Science, 2024)
Knowledge of Antarctic permafrost is mainly derived from the Antarctic Peninsula and Victoria Land. This study examines the 2019–2023 temperature and humidity conditions, distribution and development of polygonal terrain and the origin of ground ice in soils of the Untersee Oasis. In this region, the surface offset (MAAT ≅ MAGST) and the thermal offset (MAGST ≤ TTIT) reflect the lack of vegetation, absence of persistent snow and a dry soil above the ice table. The mean annual vapour pressure at the ground surface is approximately ~2× higher than in the air but is ~0.67× lower than at the ice table. The size of polygons appears to be in equilibrium with the ice-table depth, and numerical modelling suggests that the depth of the ice table is in turn in equilibrium with the ground surface temperature and humidity. The ground ice at the ice table probably originates from the partial evaporation of snowmelt that infiltrated the dry soil column. As such, the depth of the ice table in this region is set by the water vapour density gradient between the ground surface and the ice-bearing ground, but it is recharged periodically by evaporating snowmelt.
Edition: 2024/12/17 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fysisk geografi; geologi; permafrost

Hydrography and circulation below Fimbulisen Ice Shelf, East Antarctica, from 14 years of moored observations - Lauber, Julius; Hattermann, Tore; de Steur, Laura; Darelius, Elin; Fransson, Agneta (Ocean Sci., 2024)
Future mass loss from the East Antarctic Ice Sheet represents a major uncertainty in projections of future sea level rise. Recent studies have highlighted the potential vulnerability of the East Antarctic Ice Sheet to atmospheric and oceanic changes, but long-term observations inside the ice shelf cavities are rare. Here, we present new insights from observations from three oceanic moorings below Fimbulisen Ice Shelf from 2009 to 2023. We examine the characteristics of intrusions of modified Warm Deep Water (mWDW) across a sill connecting the cavity to the open ocean and investigate seasonal variability of the circulation and water masses inside the cavity using an optimum multiparameter analysis. In autumn, the water below the 345 m deep central part of the ice shelf is composed of up to 30 % solar-heated, buoyant Antarctic Surface Water (ASW), separating colder Ice Shelf Water from the ice base and affecting the cavity circulation on seasonal timescales. At depth, the occurrence of mWDW is associated with the advection of cyclonic eddies across the sill into the cavity. These eddies reach up to the ice base. The warm intrusions are observed most often from January to March and from September to November, and traces of mWDW-derived meltwater close to the ice base imply an overturning of these warm intrusions inside the cavity. We suggest that this timing is set by both the offshore thermocline depth and the interactions of the Antarctic Slope Current with the ice shelf topography over the continental slope. Our findings provide a better understanding of the interplay between shallow inflows of ASW contributions and deep inflows of mWDW for basal melting at Fimbulisen Ice Shelf, with implications for the potential vulnerability of the ice shelf to climate change.
Publisher: Copernicus Publications
Keywords: Dronning Maud Land; hydrografi; isshelf; klimaendringer; klimatologi; oseanografi

Supraglacial lake evolution and its drivers in Dronning Maud Land, East Antarctica - Mahagaonkar, Anirudha; Moholdt, Geir; Glaude, Quentin; Schuler, Thomas Vikhamar (Journal of Glaciology, 2024)
Supraglacial lakes on Antarctic ice shelves can have far-reaching implications for ice-sheet stability, highlighting the need to understand their dynamics, controls and role in the ice-sheet mass budget. We combine a detailed satellite-based record of seasonal lake evolution in Dronning Maud Land with a high-resolution simulation from the regional climate model Modèle Atmosphérique Régional to identify drivers of lake variability between 2014 and 2021. Correlations between summer lake extents and climate parameters reveal complex relationships that vary both in space and time. Shortwave radiation contributes positively to the energy budget during summer melt seasons, but summers with enhanced longwave radiation are more prone to surface melting and ponding, which is further enhanced by advected heat from summer precipitation. In contrast, previous winter precipitation has a negative effect on summer lake extents, presumably by increasing albedo and pore space, delaying the accumulation of meltwater. Downslope katabatic or föhn winds promote ponding around the grounding zones of some ice shelves. At a larger scale, we find that summers during periods of negative southern annular mode are associated with increased ponding in Dronning Maud Land. The high variability in seasonal lake extents indicates that these ice shelves are highly sensitive to future warming or intensified extreme events.
Edition: 2024/10/02 Publisher: Cambridge University Press
Keywords: Dronning Maud Land; fjernmåling; glasiologi; innlandsis; isshelf; klimamodeller; subglasial innsjø

The Troll Observing Network (TONe): A contribution to improving observations in the data-sparse region of Dronning Maud Land, Antarctica - Pedersen, Christina A.; Njåstad, Birgit; Aas, Wenche; Darelius, Elin; Descamps, Sébastien; Flått, Stig; Hattermann, Tore; Hudson, Stephen R.; Miloch, Wojciech J.; Rykkje, Simen; Schweitzer, Johannes; Storvold, Rune; et al. (Polar Research, 2024)
Understanding how Antarctica is changing and how these changes influence the rest of the Earth is fundamental to the future robustness of human society. Strengthening our understanding of these changes and their implications requires dedicated, sustained and coordinated observations of key Antarctic indicators. The Troll Observing Network (TONe), now under development, is Norway’s contribution to the global need for sustained, coordinated, complementary and societally relevant observations from Antarctica. When fully implemented within the coming three years, TONe will be a state-of-the-art, multi-platform, multi-disciplinary observing network in data-sparse Dronning Maud Land. A critical part of the network is a data management system that will ensure broad, free access to all TONe data to the international research community.
Section: Perspectives
Keywords: Antarktis; Dronning Maud Land; Sørishavet; Troll forskningsstasjon; biologi; datainnsamling; forskningsinfrastruktur; fysikk; geologi; internasjonal samarbeid; kjemi

A topographic hinge-zone divides coastal and inland ice dynamic regimes in East Antarctica - Andersen, Jane L.; Newall, Jennifer C.; Fredin, Ola; Glasser, Neil F.; Lifton, Nathaniel A.; Stuart, Finlay M.; Fabel, Derek; Caffee, Marc; Pedersen, Vivi K.; Koester, Alexandria J.; Suganuma, Yusuke; Harbor, Jonathan M.; et al. (Communications Earth & Environment, 2023)
The impact of late Cenozoic climate on the East Antarctic Ice Sheet is uncertain. Poorly constrained patterns of relative ice thinning and thickening impair the reconstruction of past ice-sheet dynamics and global sea-level budgets. Here we quantify long-term ice cover of mountains protruding the ice-sheet surface in western Dronning Maud Land, using cosmogenic Chlorine-36, Aluminium-26, Beryllium-10, and Neon-21 from bedrock in an inverse modeling approach. We find that near-coastal sites experienced ice burial up to 75–97% of time since 1 Ma, while interior sites only experienced brief periods of ice burial, generally <20% of time since 1 Ma. Based on these results, we suggest that the escarpment in Dronning Maud Land acts as a hinge-zone, where ice-dynamic changes driven by grounding-line migration are attenuated inland from the coastal portions of the East Antarctic Ice Sheet, and where precipitation-controlled ice-thickness variations on the polar plateau taper off towards the coast.
Keywords: Dronning Maud Land; glasiologi

Investigating the spatial representativeness of East Antarctic ice cores: a comparison of ice core and radar-derived surface mass balance over coastal ice rises and Dome Fuji - Cavitte, M. G. P.; Goosse, H.; Matsuoka, K.; Wauthy, S.; Goel, V.; Dey, R.; Pratap, B.; Van Liefferinge, B.; Meloth, T.; Tison, J.-L. (The Cryosphere, 2023)
Surface mass balance (SMB) of the Antarctic Ice Sheet must be better understood to document the current Antarctic contribution to sea-level rise. In situ point data using snow stakes and ice cores are often used to evaluate the state of the ice sheet's mass balance, as well as to assess SMB derived from regional climate models, which are then used to produce future climate projections. However, spatial representativeness of individual point data remains largely unknown, particularly in the coastal regions of Antarctica with highly variable terrain. Here, we compare ice core data collected at the summit of eight ice rises along the coast of Dronning Maud Land, as well as at the Dome Fuji site, and shallow ice-penetrating radar data over these regions. Shallow radar data have the advantage of being spatially extensive, with a temporal resolution that varies between a yearly and multi-year resolution, from which we can derive a SMB record over the entire radar survey. This comparison therefore allows us to evaluate the spatial variability of SMB and the spatial representativeness of ice-core-derived SMB. We found that ice core mean SMB is very local, and the difference with radar-derived SMB increases in a logarithmic fashion as the surface covered by the radar data increases, with a plateau ∼ 1–2 km away from the ice crest for most ice rises, where there are strong wind–topography interactions, and ∼ 10 km where the ice shelves begin. The relative uncertainty in measuring SMB also increases rapidly as we move away from the ice core sites. Five of our ice rise sites show a strong spatial representativeness in terms of temporal variability, while the other three sites show that it is limited to a surface area between 20–120 km2. The Dome Fuji site, on the other hand, shows a small difference between pointwise and area mean SMB, as well as a strong spatial representativeness in terms of temporal variability. We found no simple parameterization that could represent the spatial variability observed at all the sites. However, these data clearly indicate that local spatial SMB variability must be considered when assessing mass balance, as well as comparing modeled SMB values to point field data, and therefore must be included in the estimate of the uncertainty of the observations.
Keywords: Dronning Maud Land; glasiologi; isshelf; smelting

A thicker Antarctic ice stream during the mid-Pliocene warm period - Mas e Braga, Martim; Jones, Richard S.; Bernales, Jorge; Andersen, Jane Lund; Fredin, Ola; Morlighem, Mathieu; Koester, Alexandria J.; Lifton, Nathaniel A.; Harbor, Jonathan M.; Suganuma, Yusuke; Glasser, Neil F.; Rogozhina, Irina; et al. (Communications Earth & Environment, 2023)
Ice streams regulate most ice mass loss in Antarctica. Determining ice stream response to warmer conditions during the Pliocene could provide insights into their future behaviour, but this is hindered by a poor representation of subglacial topography in ice-sheet models. We address this limitation using a high-resolution model for Dronning Maud Land (East Antarctica). We show that contrary to dynamic thinning of the region’s ice streams following ice-shelf collapse, the largest ice stream, Jutulstraumen, thickens by 700 m despite lying on a retrograde bed slope. We attribute this counterintuitive thickening to a shallower Pliocene subglacial topography and inherent high lateral stresses at its flux gate. These conditions constrict ice drainage and, combined with increased snowfall, allow ice accumulation upstream. Similar stress balances and increased precipitation projections occur across 27% of present-day East Antarctica, and understanding how lateral stresses regulate ice-stream discharge is necessary for accurately assessing Antarctica’s future sea-level rise contribution.
Article number: 321
Keywords: Dronning Maud Land; glasiologi; klimaendringer; paleoklimatologi

Stochastic Simulations of Bed Topography Constrain Geothermal Heat Flow and Subglacial Drainage Near Dome Fuji, East Antarctica - Shackleton, Calvin; Matsuoka, Kenichi; Moholdt, Geir; Van Liefferinge, Brice; Paden, John (Journal of Geophysical Research: Earth Surface, 2023)
Abstract Topographic variability beneath ice sheets regulates ice flow, basal melting, refreezing processes, and meltwater drainage. The preservation of old ice layers and basal ice stratigraphy is sensitive to these subglacial processes, and Dome Fuji, inland East Antarctica, is one of the few regions where 1.5-Ma old ice can be preserved for investigating a major climatic change that occurred in the mid-Pleistocene. We used stochastic simulation methods and radar data to generate an ensemble of simulated bed topography with the continuous and realistic roughness necessary to assess basal conditions. Ensemble analysis reveals the magnitude and spatial distribution of topographic uncertainty, facilitating uncertainty-constrained assessments of subglacial drainage and topographic adjustments to geothermal heat flow (GHF). We find that topographic variability can lead to widespread local GHF variations of ±20% of the background value, which aggregate to raise the regional value and suggest previously underestimated distributions and rates of basal melting. We also find that survey profile spacing has an increasing influence on topographic uncertainty for rougher bed, deriving an empirical relationship that could guide future survey planning based on uncertainty tolerance.
_eprint: https://agupubs.onlinelibrary.wiley.com/doi/pdf/10.1029/2023JF007269
Keywords: Dronning Maud Land; glasiologi; hydrologi

Bioaccumulation of Per and Polyfluoroalkyl Substances in Antarctic Breeding South Polar Skuas (Catharacta maccormicki) and Their Prey - Alfaro Garcia, Laura Andrea; Descamps, Sébastien; Herzke, Dorte; Chastel, Olivier; Carravieri, Alice; Cherel, Yves; Labadie, Pierre; Budzinski, Hélène; Munoz, Gabriel; Bustamante, Paco; Polder, Anuschka; Gabrielsen, Geir Wing; et al. (Frontiers in Marine Science, 2022)
Per and polyfluoroalkyl substances (PFASs) are found in Antarctic wildlife, with high levels in the avian top predator south polar skua (Catharacta maccormicki). As increasing PFAS concentrations were found in the south polar skua during the breeding season in Antarctica, we hypothesised that available prey during the breeding period contributes significantly to the PFAS contamination in skuas. To test this, we compared PFAS in south polar skuas and their main prey from two breeding sites on opposite sides of the Antarctic continent: Antarctic petrel (Thalassoica antarctica) stomach content, eggs, chicks, and adults from Svarthamaren in Dronning Maud Land and Adélie penguin chicks (Pygoscelis adeliae) from Dumont d’Urville in Adélie Land. Of the 22 PFAS analysed, seven were present in the majority of samples, except petrel stomach content [only perfluoroundecanoate (PFUnA) present] and Adélie penguins (only four compounds present), with increasing concentrations from the prey to the skuas. The biomagnification factors (BMFs) were higher at Dumont d’Urville than Svarthamaren. When adjusted to reflect one trophic level difference, the BMFs at Svarthamaren remained the same, whereas the ones at Dumont d’Urville doubled. At both the colonies, the skua PFAS pattern was dominated by perfluorooctanesulfonic acid (PFOS), followed by PFUnA, but differed with the presence of branched PFOS and perfluorotetradecanoate (PFTeA) and lack of perfluorononanoate (PFNA) and perfluorodecanoate (PFDA) at Dumont d’Urville. At Svarthamaren, the pattern in the prey was comparable to the skuas, but with a higher relative contribution of PFTeA in prey. At Dumont d’Urville, the pattern in the prey differed from the skuas, with the domination of PFUnA and the general lack of PFOS in prey. Even though the PFAS levels are low in Antarctic year-round resident prey, the three lines of evidence (pattern, BMF difference, and BMF adjusted to one trophic level) suggest that the Antarctic petrel are the significant source of PFAS in the Svarthamaren skuas, whereas the skuas in Dumont d’Urville have other important sources to PFAS than Adélie penguin, either in the continent or external on the inter-breeding foraging grounds far from Antarctica.
Keywords: Antarktis; Dronning Maud Land; biologi; ornitologi; petreller; sjøfugler

Variation in Antarctic Petrel Foraging Ecology: Not All Individuals Specialize on Krill - Descamps, Sébastien; Harris, Stephanie; Fluhr, Julie; Bustamante, Paco; Cherel, Yves; Trevail, Alice; Brault-Favrou, Maud; Patrick, Samantha (Frontiers in Marine Science, 2022)
Individual heterogeneity in foraging behaviour determines how individuals and populations respond to changes in the availability and distribution of resources. Antarctic krill Euphausia superba is a pivotal species in Southern Ocean food webs and an important target for Southern Ocean fisheries. Changes in its abundance could dramatically impact marine predators, with effects depending on the extent to which all individuals rely on krill as prey. The Antarctic petrel Thalassoica antarctica is a high latitude seabird thought to be dependent on krill in part of its breeding range. Here, by combining fine-scale GPS tracking of petrel foraging trips with diet data, we examined the level and consistency of inter-individual variation in foraging strategies in breeding Antarctic petrels in Dronning Maud Land, Antarctica, and assessed whether all individuals share a similar reliance on Antarctic krill. We found that Antarctic petrels showed high levels of repeatability in their diet and foraging movements at sea, indicating consistent individual differences in foraging strategies. During consecutive foraging trips, petrels tend to make trips of similar lengths and durations to reach similar terminal locations and to feed on similar prey. These individual differences in diet were spatially structured, with individuals travelling towards the west consuming a more fish-based diet. These different foraging tactics did not appear to be associated with different costs and/or benefits as adult body mass, chick survival and chick growth were unrelated to birds’ foraging movements and diet. Our results show that, even if a large part of the population may be dependent on krill, some individuals specialize on fish. Such inter-individual variation in foraging suggests that this population could be more resilient to changes in the marine environment, such as a decline in krill abundance or a shift in krill distributions.
Keywords: Dronning Maud Land; biologi; ornitologi; petreller; sjøfugler; zoologi

Cavernous Decay of Granite and Granitic Gneiss, Central Dronning Maud Land, Antarctica - Engvik, Ane K; Elvevold, Synnøve; Myhre, Per Inge (The Journal of Geology, 2022)
Tafoni are a type of cavernous weathering that is found in a variety of rock types and locations around the world. Tafoni have been documented in a number of climatic zones ranging from hot and cold deserts to moist coastal environments. Despite the widespread distribution of tafoni, the major processes controlling tafoni weathering are not well understood and are still a matter of discussion. This study addresses the frequent distribution of well-developed tafoni in the cold, arid environment of the inland mountain range of central Dronning Maud Land, Antarctica. The aim is to document and characterize the nature of tafoni present in Gjelsvikfjella (2°E) eastward to Filchnerfjella (8°E) and to discuss formation processes. The cavities occur in groups and are typically spherical to oval shaped. They range in diameter and depth from 1 dm up to 1.5 m. The cold, arid environment of this region favors mechanical weathering mechanisms such as freeze-thaw actions and wind abrasion. Furthermore, the structural, textural, and mineralogical properties of the parent rock can potentially have a strong control on weathering and cavity development. Observed tafoni are typically formed in massive granitoid intrusives and granitic gneisses and migmatites. Chemical dissolution of pyroxene to iddingsite and radiation from rare earth element–bearing accessory minerals cause microfracturing, which facilitates freeze-thaw actions and accordingly enhances the weathering.
Keywords: Dronning Maud Land; geologi

Synthesis of field and satellite data to elucidate recent mass balance of five ice rises in Dronning Maud Land, Antarctica - Goel, Vikram; Morris, Ashley; Moholdt, Geir; Matsuoka, Kenichi (Frontiers in Earth Science, 2022)
We investigated mass balance changes over five ice rises in the last few decades near Fimbul and Nivl ice shelves in central Dronning Maud Land. We use the Input-Output Method constrained using field-based geophysical measurements conducted during the austral summers of 2012–14 over three ice rises near the Fimbul Ice Shelf. Further, we use satellite altimetry data (ICESat, ICESat-2, and CryoSat-2) to estimate geodetic mass balance over all five ice rises in recent decades. Both field- and satellite-based estimates show that until 2010, three out of five ice rises were thickening (0.4–0.2 m_ieq a^−1) while two were close to balance. However, over the last decade, the ice rises thickening previously started to thin (−0.2–−0.6 m_ieq a^−1) while the other two remained close to balance. Much of this variability is likely associated with regional surface mass balance trends, with each ice rise exhibiting its characteristics depending on its local glaciological settings.
Keywords: Dronning Maud Land; geofysikk; glasiologi

A review of the scientific knowledge of the seascape off Dronning Maud Land, Antarctica - Lowther, Andrew; von Quillfeldt, Cecilie; Assmy, Philipp; De Steur, Laura; Descamps, Sebastien; Divine, Dmitry; Elvevold, Synnøve; Forwick, Matthias; Fransson, Agneta; Fraser, Alexander; Gerland, Sebastian; Granskog, Mats; et al. (Polar Biology, 2022)
Despite the exclusion of the Southern Ocean from assessments of progress towards achieving the Convention on Biological Diversity (CBD) Strategic Plan, the Commission for the Conservation of Antarctic Marine Living Resources (CCAMLR) has taken on the mantle of progressing efforts to achieve it. Within the CBD, Aichi Target 11 represents an agreed commitment to protect 10% of the global coastal and marine environment. Adopting an ethos of presenting the best available scientific evidence to support policy makers, CCAMLR has progressed this by designating two Marine Protected Areas in the Southern Ocean, with three others under consideration. The region of Antarctica known as Dronning Maud Land (DML; 20°W to 40°E) and the Atlantic sector of the Southern Ocean that abuts it conveniently spans one region under consideration for spatial protection. To facilitate both an open and transparent process to provide the vest available scientific evidence for policy makers to formulate management options, we review the body of physical, geochemical and biological knowledge of the marine environment of this region. The level of scientific knowledge throughout the seascape abutting DML is polarized, with a clear lack of data in its eastern part which is presumably related to differing levels of research effort dedicated by national Antarctic programmes in the region. The lack of basic data on fundamental aspects of the physical, geological and biological nature of eastern DML make predictions of future trends difficult to impossible, with implications for the provision of management advice including spatial management. Finally, by highlighting key knowledge gaps across the scientific disciplines our review also serves to provide guidance to future research across this important region.
Keywords: Dronning Maud Land; Sørishavet; biofysikk; biogeokjemi; biologi; oseanografi

Geologisk feltarbeid i Antarktis - Sunde, Øyvind; Elvevold, Synnøve; Engvik, Ane K.; Tholfsen, Audun (Geonytt : et medlemsblad for Norsk geologisk forening, 2022)
Dronning Maud Land, som er Norges territoriale krav i Antarktis, utgjør nærmere 1/6 av det antarktiske kontinentet. Geologisk kartlegging og forskning i Dronning Maud Land er en nasjonal oppgave og i Antarktis-sammenheng kan det betraktes som en måte å vise fortsatt interesse i Norges territoriale krav.
Publisher: Norsk Geologisk Forening
Keywords: Dronning Maud Land; geologi

Banded Charnockite: The Result of Crustal Magma Generation, Piecemeal Emplacement, and Fluid-Driven Mineral Replacement in High-Grade Crust (Central Dronning Maud Land, Antarctica) - Engvik, Ane K.; Corfu, Fernando; Kleinhanns, Ilka C.; Elvevold, Synnøve (The Journal of Geology, 2021)
AbstractOur study of a banded charnockite complex of the Mühlig-Hofmannfjella in Dronning Maud Land, Antarctica, illustrates how the combination of high-temperature (re-)crystallization processes, melts, and volatile fluids leads to complex intrusive, metasomatic, and structural relationships. The igneous complex consists of gently dipping sets of charnockite interlayered with dolerite and leucogranite. The banded complex formed primarily by magmatic processes, but with superimposed modifications by metasomatism. The charnockite has a ferroan composition and contains both orthopyroxene (Fs80?84) and olivine (Fa94?96). Zircon U-Pb dates the emplacement of charnockite at 515 Ma, and inherited zircon cores and negative εNd values of ?3 to ?5 indicate that the age of the source of the magma was about 1100 Ma. Neodymium isotopes were not homogenized during the Cambrian magmatic event, which suggests that the generation and emplacement of the magma took place in separate batches during construction of the banded complex. By contrast, the Rb-Sr system in the charnockite was extensively homogenized, likely because of the superimposed late-magmatic fluid activity, which also produced the bands and networks of leucogranites. These events occurred during the late stages of the assembly of Gondwana, with postcollisional extension and mantle upwelling maintaining a high heat flow.
Publisher: The University of Chicago Press
Keywords: Dronning Maud Land; geologi

Brominated Flame Retardants in Antarctic Air in the Vicinity of Two All-Year Research Stations - Bengtson Nash, Susan Maria; Wild, Seanan; Broomhall, Sara; Bohlin-Nizzetto, Pernilla (Atmosphere, 2021)
Continuous atmospheric sampling was conducted between 2010–2015 at Casey station in Wilkes Land, Antarctica, and throughout 2013 at Troll Station in Dronning Maud Land, Antarctica. Sample extracts were analyzed for polybrominated diphenyl ethers (PBDEs), and the naturally converted brominated compound, 2,4,6-Tribromoanisole, to explore regional profiles. This represents the first report of seasonal resolution of PBDEs in the Antarctic atmosphere, and we describe conspicuous differences in the ambient atmospheric concentrations of brominated compounds observed between the two stations. Notably, levels of BDE-47 detected at Troll station were higher than those previously detected in the Antarctic or Southern Ocean region, with a maximum concentration of 7800 fg/m3. Elevated levels of penta-formulation PBDE congeners at Troll coincided with local building activities and subsided in the months following completion of activities. The latter provides important information for managers of National Antarctic Programs for preventing the release of persistent, bioaccumulative, and toxic substances in Antarctica.
Keywords: Dronning Maud Land; Troll forskningsstasjon; atmosfæren; menneskelig påvirkning; miljøgifter; miljøovervåking; målinger

Trophic and fitness correlates of mercury and organochlorine compound residues in egg-laying Antarctic petrels - Carravieri, Alice; Warner, Nicholas A; Herzke, Dorte; Brault-Favrou, Maud; Tarroux, Arnaud; Fort, Jérôme; Bustamante, Paco; Descamps, Sébastien (Environmental Research, 2021)
Understanding the drivers and effects of exposure to contaminants such as mercury (Hg) and organochlorine compounds (OCs) in Antarctic wildlife is still limited. Yet, Hg and OCs have known physiological and fitness effects in animals, with consequences on their populations. Here we measured total Hg (a proxy of methyl-Hg) in blood cells and feathers, and 12 OCs (seven polychlorinated biphenyls, PCBs, and five organochlorine pesticides, OCPs) in plasma of 30 breeding female Antarctic petrels Thalassoica antarctica from one of the largest colonies in Antarctica (Svarthamaren, Dronning Maud Land). This colony is declining and there is poor documentation on the potential role played by contaminants on individual physiology and fitness. Carbon (δ13C) and nitrogen (δ15N) stable isotope values measured in the females' blood cells and feathers served as proxies of their feeding ecology during the pre-laying (austral spring) and moulting (winter) periods, respectively. We document feather Hg concentrations (mean ± SD, 2.41 ± 0.83 μg g−1 dry weight, dw) for the first time in this species. Blood cell Hg concentrations (1.38 ± 0.43 μg g−1 dw) were almost twice as high as those reported in a recent study, and increased with pre-laying trophic position (blood cell δ15N). Moulting trophic ecology did not predict blood Hg concentrations. PCB concentrations were very low (Σ7PCBs, 0.35 ± 0.31 ng g−1 wet weight, ww). Among OCPs, HCB (1.02 ± 0.36 ng g−1 ww) and p, p’-DDE (1.02 ± 1.49 ng g−1 ww) residues were comparable to those of ecologically-similar polar seabirds, while Mirex residues (0.72 ± 0.35 ng g−1 ww) were higher. PCB and OCP concentrations showed no clear relationship with pre-laying or moulting feeding ecology, indicating that other factors overcome dietary drivers. OC residues were inversely related to body condition, suggesting stronger release of OCs into the circulation of egg-laying females upon depletion of their lipid reserves. Egg volume, hatching success, chick body condition and survival were not related to maternal Hg or OC concentrations. Legacy contaminant exposure does not seem to represent a threat for the breeding fraction of this population over the short term. Yet, exposure to contaminants, especially Mirex, and other concurring environmental stressors should be monitored over the long-term in this declining population.
Keywords: Dronning Maud Land; forurensning; miljøendringer; miljøgifter; ornitologi; petreller; sjøfugler

Moving mountains - when rocks and fluids interact - Engvik, Ane K.; Elvevold, Synnøve; Myhre, Per Inge; Sunde, Øyvind; Austrheim, Håkon (Fram forum, 2021)
Keywords: Dronning Maud Land; fjellene; forskning; geologi; mineralogi; nunataker

Substantial spatial variation in glacial erosion rates in the Dronning Maud Land Mountains, East Antarctica - Sirevaag, Hallgeir; Jacobs, Joachim; Ksienzyk, Anna K (Communications Earth & Environment, 2021)
The coast-parallel Dronning Maud Land (DML) mountains represent a key nucleation site for the protracted glaciation of Antarctica. Their evolution is therefore of special interest for understanding the formation and development of the Antarctic ice sheet. Extensive glacial erosion has clearly altered the landscape over the past 34 Myr. Yet, the total erosion still remains to be properly constrained. Here, we investigate the power of low-temperature thermochronology in quantifying glacial erosion in-situ. Our data document the differential erosion along the DML escarpment, with up to c. 1.5 and 2.4 km of erosion in western and central DML, respectively. Substantial erosion at the escarpment foothills, and limited erosion at high elevations and close to drainage divides, is consistent with an escarpment retreat model. Such differential erosion suggests major alterations of the landscape during 34 Myr of glaciation and should be implemented in future ice sheet models.
Keywords: Dronning Maud Land; geologi; geomorfologi

Satellite and ground based estimates for ice surface velocities in the part of central Dronning Maud Land, East Antarctica: Implications for ice flux calculations - Thakur, Praveen K; Swain, Ashit K; Dhote, Pankaj R; Kumar, Pradeep; Kaushik, Suvrat; Gajbhiye, Deepak; Mahagaonkar, Anirudha; Sharma, Vishal; Dharwadkar, Amit; Aggarwal, S P; Beg, Javed; Chauhan, Prakash; et al. (Polar Science, 2021)
The ice sheet and glaciers of Antarctica and Greenland represent the largest sources of freshwater on planet Earth. The understanding and quantification of their dynamic properties such as albedo, precipitation, ice mass movement, and ice elevation changes are critical for the improved climate and mass balance models. The present study utilizes space-borne optical and synthetic aperture radar (SAR) imagery to measure the ice surface velocity at high spatial resolution for a part of the central Dronning Maud Land (cDML), East Antarctica. The datasets from Landsat-8 and Sentinel-1 SAR satellite are used for ice stream velocity estimation using feature-offset tracking and differential interferometric SAR (DInSAR) methods. The derived velocity products are validated with ground based stakes network at annual time scale. The fundamental ice flow laws are used to estimate the ice outflux or discharge for selected ice stream drainage basins of cDML at fluxgate locations. The ice stream basin has been delineated using combination of elevation, slope and continental scale velocity maps. The ice influx for study area is estimated using ECMWF fifth generation reanalysis (ERA5) and Regional Atmospheric Climate Model (RACMO) v2.3 model outputs. The estimated influx and outflux are in the ranges of 0.18–4.167 Gt/y and 0.201 to 1.278 Gt/y respectively, indicating net positive mass balance for the selected area.
Keywords: Dronning Maud Land; glasiologi; innlandsis; polarområdene

Ice surface changes during recent glacial cycles along the Jutulstraumen and Penck Trough ice streams in western Dronning Maud Land, East Antarctica - Andersen, J.L.; Newall, J.C.; Blomdin, R.; Sams, S.E.; Fabel, D.; Koester, A.J.; Lifton, N.A.; Fredin, O.; Caffee, M.W.; Glasser, Neil F.; Rogozhina, I.; Suganuma, Y.; et al. (Quaternary Science Reviews, 2020)
Reconstructing past ice-sheet surface changes is key to testing and improving ice-sheet models. Data constraining the past behaviour of the East Antarctic Ice Sheet are sparse, limiting our understanding of its response to past, present and future climate change. Here, we report the first cosmogenic multi-nuclide (10Be, 26Al, 36Cl) data from bedrock and erratics on nunataks along the Jutulstraumen and Penck Trough ice streams in western Dronning Maud Land, East Antarctica. Spanning elevations between 741 and 2394 m above sea level, the samples have apparent exposure ages between 2 ka and 5 Ma. The highest-elevation bedrock sample indicates (near-) continuous minimum exposure since the Pliocene, with a low apparent erosion rate of 0.15 ± 0.03 m Ma−1, which is similar to results from eastern Dronning Maud Land. In contrast to studies in eastern Dronning Maud Land, however, our data show clear indications of a thicker-than-present ice sheet within the last glacial cycle, with a thinning of ∼35–120 m during the Holocene (∼2–11 ka). Difficulties in separating suitable amounts of quartz from the often quartz-poor rock-types in the area, and cosmogenic nuclides inherited from exposure prior to the last deglaciation, prevented robust thinning estimates from elevational profiles. Nevertheless, the results clearly demonstrate ice-surface fluctuations of several hundred meters between the current grounding line and the edge of the polar plateau for the last glacial cycle, a constraint that should be considered in future ice-sheet model simulations.
Keywords: Antarctica; Cosmogenic isotopes; Dronning Maud Land; Glaciation; Quaternary; glasiologi

Prolonged high-grade metamorphism of supracrustal gneisses from Mühlig-Hofmannfjella, central Dronning Maud Land (East Antarctica) - Elvevold, Synnøve; Engvik, Ane K.; Abu-Alam, Tamer S.; Myhre, Per Inge; Corfu, Fernando (Precambrian Research, 2020)
The bedrock of Mühlig-Hofmannfjella, central Dronning Maud Land in eastern Antarctica, is part of the high-grade Maud Belt and comprises a deep-seated metamorphic-plutonic complex. The P-T-t evolution of anatectic supracrustal gneisses has been recovered through a study of mineral assemblages, textural relationships and U-Pb ID TIMS geochronology on zircon and monazite followed by pseudosection modelling. Peak conditions reached granulite facies conditions (T ≥ 810–820 °C) at moderate crustal depths (P = ca. 8 kbar) and resulted in partial melting. Peak-pressure conditions were followed by isothermal decompression at elevated temperatures. After exhumation to crustal levels of about 4–5 kbar, the area underwent a final near-isobaric cooling, which is documented by a secondary growth of garnet. Zircons indicate a period of growth at 570–566 Ma, whereas monazite ages range from 610 to 525 Ma. A likely heat source for the granulite facies metamorphism is decay of radioactive heat-producing elements in the core of the orogen. The combined geochronology and metamorphic data indicate a prolonged, clockwise P-T path, which reflects collision and formation of a long-lived orogenic plateau.
Article number: 105618
Keywords: Antarktis; Dronning Maud Land; geologi

Neoproterozoic geodynamic evolution of easternmost Kalahari: Constraints from U-Pb-Hf-O zircon, Sm-Nd isotope and geochemical data from the Schirmacher Oasis, East Antarctica - Jacobs, Joachim; Mikhalsky, Evgeny; Henjes-Kunst, Friedhelm; Läufer, Andreas; Thomas, Robert J; Elburg, Marlina; Wang, Chengcheng; Estrada, Solveig; Skublov, S G (Precambrian Research, 2020)
Late Tonian (ca. 785–760 Ma) granodioritic to granitic orthogneisses of the Schirmacher Oasis region in Dronning Maud Land (DML), East Antarctica, are interpreted as recording an active continental margin setting at the periphery of Kalahari and Rodinia. The rocks probably represent exposures of a significant tectonic province hidden beneath the ice, the erosional remnants of which are recorded as detrital zircons in late Tonian-Cryogenian metasedimentary rocks throughout central and eastern DML, as well as in ice-rafted debris from recent sediments offshore Dronning Maud Land. The orthogneisses have single-stage Sm-Nd model ages of ca. 1.3–1.5 Ga and zircon Hf-signatures (εHft = +2 – +5), indistinguishable from the adjacent Grenville-age basement rocks of easternmost Kalahari. Their geochemistry suggests that they evolved in the late stages of a continental margin magmatic arc and possibly within a roll-back tectonic framework, suggestive of subduction of relatively old oceanic lithosphere. The eastern Kalahari continental arc is one of a number of continental arcs that characterize the western part of the fragmenting Rodinia and document the supercontinent “turning inside out” after its formation at ca. 1000 Ma and a period of relative tectonic quiescence between ca. 900 and 800 Ma. The rocks show an ultra-high temperature metamorphic overprint that was accompanied by syn-tectonic magmatism from ca. 650 to 600 Ma. The high temperature metamorphism is interpreted to relate to back-arc extension that also led to major anorthosite magmatism elsewhere, prior to continental collision in the region. The rocks lack the subsequent widespread high-grade metamorphic overprint at ca. 590–500 Ma which occurs in the adjacent regions due to Himalayan-style continental collision along the East African-Antarctic Orogen during Gondwana assembly.
Keywords: Dronning Maud Land; geokronologi; geologi

The glacial geomorphology of western Dronning Maud Land, Antarctica - Newall, Jennifer C H; Dymova, Taisiya; Serra, Elena; Blomdin, Robin; Fredin, Hans Ola; Glasser, Neil F; Suganuma, Yusuke; Harbor, Jonathan M; Stroeven, Arjen P (Journal of Maps, 2020)
Reconstructing the response of present-day ice sheets to past global climate change is important for constraining and refining the numerical models which forecast future contributions of these ice sheets to sea-level change. Mapping landforms is an essential step in reconstructing glacial histories. Here we present a new map of glacial landforms and deposits on nunataks in western Dronning Maud Land, Antarctica. Nunataks are mountains or ridges that currently protrude through the ice sheet and may provide evidence that they have been wholly or partly covered by ice, thus indicating a formerly more extensive (thicker) ice sheet. The map was produced through a combination of mapping from Worldview satellite imagery and ground validation. The sub-metre spatial resolution of the satellite imagery enabled mapping with unprecedented detail. Ten landform categories have been mapped, and the landform distributions provide evidence constraining spatial patterns of a previously thicker ice sheet.
Publisher: Taylor & Francis
Keywords: Dronning Maud Land; geomorfologi; innlandsis; klimaendringer; nunataker; paleoglasiologi

Ionosfæriske scintillasjoner på GNSS-signaler over Dronning Maud Land, Antarktis: statistikk og kasusstudier - Skjæveland, Arnlaug Høgås (Universitetet i Oslo, 2020)
I denne oppgaven er forekomsten av fasescintillasjoner på GNSS-signaler over deler av Dronning Maud Land i Antarktis kartlagt, ved bruk av scintillasjonsmottakere på Troll stasjonen (geografiske koordinater: 72.0◦S, 2.5◦Ø, magnetiske koordinater: 62.8◦S, 47.8◦Ø) og SANAE IV (geografiske koordinater: 71.7◦S, 2.8◦V, magnetiske koordinater: 62.0◦S, 45.0◦Ø). Ionosfæren i dette området er lite studert tidligere, og dette er de første resultatene som presenteres fra det nylig etablerte Troll ionosfæriske observatoriet. Den første delen av oppgaven er en statistisk studie hvor forekomsten av scintillasjoner i 2018 er kartlagt. Hovedfunnet i denne studien er at høye fasescintillasjoner kun forekommer ved høy geomagnetisk aktivitet, forekomsten av scintillasjoner er høyere postmidnatt enn premidnatt og at scintillasjoner forekommer både innenfor og nord for den statistiske auroraovalen. I denne oppgaven er det også gjennomført to kasusstudier, en fra februar 2018 og en fra mars 2018. Kasusstudiene brukte satellittdata fra solvinden, Swarm, DMSP og bakkebaserte instrumenter: scintillasjonsmottakere, magnetometere og Superdarn, fra både den nordlige og sørlige halvkule. Hovedfunnene fra kasusstudiene er at scintillasjoner på Troll og Sanae kan assosieres med partikkelnedbør, sterke vestgående strømmer og høye konveksjonshastigheter. De viste også en hvis symmetri i forekomsten av scintillasjoner, men scintillasjonene var kraftigere og var til stede over en lengre tidsperiode i Antarktis enn på Færøyene.
Publication Title: Institutt for fysikk. Det matematisk-naturvitenskapelige fakultet Volume: M.Sc.
Keywords: Antarktis; Dronning Maud Land; Troll forskningsstasjon; aurora; geomagnetiske stormer; ionosfæren; romfysikk; sørlys

Detailed Seismic Bathymetry Beneath Ekström Ice Shelf, Antarctica: Implications for Glacial History and Ice-Ocean Interaction - Smith, Emma C; Hattermann, Tore; Kuhn, Gerhard; Gaedicke, Christoph; Berger, Sophie; Drews, Reinhard; Ehlers, Todd A; Franke, Dieter; Gromig, Rapahel; Hofstede, Coen; Lambrecht, Astrid; Läufer, Andreas; et al. (Geophysical Research Letters, 2020)
The shape of ice shelf cavities are a major source of uncertainty in understanding ice-ocean interactions. This limits assessments of the response of the Antarctic ice sheets to climate change. Here we use vibroseis seismic reflection surveys to map the bathymetry beneath the Ekström Ice Shelf, Dronning Maud Land. The new bathymetry reveals an inland-sloping trough, reaching depths of 1,100 m below sea level, near the current grounding line, which we attribute to erosion by palaeo-ice streams. The trough does not cross-cut the outer parts of the continental shelf. Conductivity-temperature-depth profiles within the ice shelf cavity reveal the presence of cold water at shallower depths and tidal mixing at the ice shelf margins. It is unknown if warm water can access the trough. The new bathymetry is thought to be representative of many ice shelves in Dronning Maud Land, which together regulate the ice loss from a substantial area of East Antarctica.
Keywords: Dronning Maud Land; batymetri; brehylle; glasiologi; havnivåstigning; innlandsis; isbrem; issmelting; klimaendringer; kontinentalsokkel; seismologi

Ground-based measurements of total ozone column amount with a multichannel moderate-bandwidth filter instrument at the Troll research station, Antarctica - Sztipanov, Milos; Tumeh, Lubna; Li, Wei; Svendby, Tove; Kylling, Arve; Dahlback, Arne; Stamnes, Jakob J; Hansen, Georg; Stamnes, Knut (Applied Optics, 2020)
Combining information from several channels of the Norwegian Institute for Air Research (NILU-UV) irradiance meter, one may determine the total ozone column (TOC) amount. A NILU-UV instrument has been deployed and operated on two locations at Troll research station in Jutulsessen, Queen Maud Land, Antarctica, for several years. The method used to determine the TOC amount is presented, and the derived TOC values are compared with those obtained from the Ozone Monitoring Instrument (OMI) located on NASA’s AURA satellite. The findings show that the NILU-UV TOC amounts correlate well with the results of the OMI and that the NILU-UV instruments are suitable for monitoring the long-term change and development of the ozone hole. Because of the large footprint of OMI, NILU-UV is a more suitable instrument for local measurements.
Publisher: OSA
Keywords: Dronning Maud Land; Troll forskningsstasjon; meteorologi; overvåkning; ozonhull; ozonlaget; ultrafiolett stråling

Late Neoproterozoic–Cambrian magmatism in Dronning Maud Land (East Antarctica): U–Pb zircon geochronology, isotope geochemistry and implications for Gondwana assembly - Wang, Cheng-Cheng; Jacobs, Joachim; Elburg, Marlina A.; Läufer, Andreas; Elvevold, Synnøve (Precambrian Research, 2020)
Dronning Maud Land (DML) is a key area for the better understanding of the geotectonic history and amalgamation processes of the southern part of Gondwana. Here, we present comprehensive new zircon U–Pb–Hf–O, whole-rock Sm–Nd isotopic and geochemical data for late Neoproterozoic-Cambrian igneous rocks along a profile from central to eastern DML, which provides new insights into the crustal evolution and tectonics of the region. In central DML, magmatism dominantly occurred at 530–485 Ma, with 650–600 Ma charnockite and anorthosite locally distributed at its eastern periphery. In contrast, eastern DML experienced long-term and continuous granitic magmatism from ca. 650 Ma to 500 Ma. In central DML, the 650–600 Ma samples are characterized by highly elevated δ18O (7.5–9.5‰) associated with slightly negative to positive εHf(t) values (−1 to +3), indicating significant addition of high-δ18O crustal components, such as sedimentary material at the margin of the Kalahari Craton. Evolved Hf isotopic signatures (εHf(t) = −15 to −6) and moderately elevated O isotopic data (δ18O = 6–8‰) of the Cambrian granitic rocks from central DML indicate a significant incorporation of the pre-existing, old continental crust. In eastern DML, the suprachondritic Hf–Nd isotope signatures and moderate δ18O values of the late Neoproterozoic granites (650–550 Ma) from the Sør Rondane Mountains support the view that they mainly originated from crust of the Tonian Oceanic Arc Super Terrane (TOAST). The post-540 Ma granites, however, have more evolved Hf and Nd isotopic compositions, suggesting an increasing involvement of older continental components during Cambrian magmatism. Nd isotopes of the Cambrian granitic rocks in DML display an increasingly more radiogenic composition towards the east with model ages ranging from late Archean to Mesoproterozoic times, which is in line with the isotopic trend of the Precambrian basement in this region. The late Neoproterozoic (>600 Ma) igneous rocks in central and eastern DML were emplaced in two independent subduction systems, at the periphery of the eastern Kalahari Craton and somewhere within the Mozambique Ocean respectively. The accretion and assembly of the TOAST to the eastern margin of the Kalahari Craton and their collision with surrounding continental blocks was followed by extensive post-collisional magmatism due to delamination tectonics and orogenic collapse in the Cambrian. The late Neoproterozoic–Cambrian igneous rocks in DML thus record an orogenic cycle from subduction-accretion, continental collision to post-collisional process during and after the assembly of Gondwana.
Article number: 105880
Keywords: Dronning Maud Land; geokjemi; geokronologi; geologi

Grenville-age continental arc magmatism and crustal evolution in central Dronning Maud Land (East Antarctica): Zircon geochronological and Hf–O isotopic evidence - Wang, Cheng-Cheng; Jacobs, Joachim; Elburg, Marlina A.; Läufer, Andreas; Thomas, Robert J.; Elvevold, Synnøve (Gondwana Research, 2020)
This study focusses on the Grenville-age Maud Belt in Dronning Maud Land (DML), East Antarctica, which was located at the margin of the Proto-Kalahari Craton during the assembly of Rodinia. We present new U–Pb zircon ages and Hf–O isotope analyses of mafic and granitic gneisses exposed in the Orvin-Wohlthat Mountains and Gjelsvikfjella, central DML (cDML). The geochronological data indicate continuous magmatic activity from 1160 to 1070 Ma which culminated at 1110–1090 Ma, followed by high-grade metamorphism between 1080 and 1030 Ma. The majority of zircons from the Orvin-Wohlthat Mountains exhibit radiogenic Hf isotopic compositions corresponding to suprachondritic εHf (t) values and Mesoproterozoic model ages, indicating crystallization from predominantly juvenile magmas. However, the involvement of ancient sedimentary material, which were most likely derived from the adjacent Proto-Kalahari Craton, is revealed by a few samples with negative to neutral εHf (t) and significantly elevated δ18O values (8–10‰). Samples from further west, in Gjelsvikfjella have more mantle-like zircon O isotopic compositions and late Paleoproterozoic Hf model ages, indicating the incorporation of ancient, previously mantle-derived continental crust. The rocks in cDML, thus define part of an extensive Mesoproterozoic magmatic arc with subduction under the Proto-Kalahari margin. This involved significant growth of new continental crust, possibly related to slab retreat, accompanied by subordinate recycling of older crustal components. The Maud Belt has previously been correlated with the 1250–1030 Ma Natal Belt in southern Africa, which lay to the west in the context of Gondwana, although this assertion has recently been questioned. Our study supports the latter view in demonstrating that the continental arc magmatism in the Maud Belt appears to be temporally and tectonically unconnected to the accretion of (slightly older) juvenile oceanic islands in the Natal Belt, which, in contrast to the Maud Belt, show subduction polarity away from the craton. We thus speculate that the Namaqua-Natal to Maud Belt contact (exposed in the Heimefront Shear Zone) may represent a changed tectonic environment from arc/continent-continent collision to slightly younger continental margin orogenesis at the westernmost termination of this part of the global Grenville Orogen. The Maud Belt marks the beginning of a major, long-lived accretionary Andean-type tectonic regime on the eastern margin of Proto-Kalahari in the Meso-Neoproterozoic during Rodinia assembly and break-up until the formation of Gondwana.
Keywords: Dronning Maud Land; geologi